PENGEMBANGAN MODUL AJAR BERBASIS WEB MENGGUNAKAN GOOGLE SITES PADA MATERI PERILAKU KONSUMEN KELAS X BISNIS DIGITAL SMKN 4 SURABAYA - Dinda Melati Putri; Finisica Dwijayati Patrikha (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
The rapid development of information technology demands the education sector to continuously innovate in delivering learning materials. This study aims to develop a web-based learning module to improve students' learning outcomes using the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The research subjects were students of class X Digital Business 1 at SMKN 4 Surabaya. The research instruments included expert validation by subject matter experts, media experts, and language experts, as well as student responses collected through questionnaires. Data analysis was carried out using descriptive qualitative and quantitative methods. The result of this study is a web-based learning module using Google Sites on consumer behavior material. The product feasibility received a